The PASTA domains of Bacillus subtilis PBP2B strengthen the interaction of PBP2B with DivIB - Morales Angeles, Danae (Microbiology (Reading), 2020)
Bacterial cell division is mediated by a protein complex known as the divisome. Many protein–protein interactions in the divisome have been characterized. In this report, we analyse the role of the PASTA (Penicillin-binding protein And Serine Threonine kinase Associated) domains of Bacillus subtilis PBP2B. PBP2B itself is essential and cannot be deleted, but removing the PBP2B PASTA domains results in impaired cell division and a heat-sensitive phenotype. This resembles the deletion of divIB, a known interaction partner of PBP2B. Bacterial two-hybrid and co-immunoprecipitation analyses show that the interaction between PBP2B and DivIB is weakened when the PBP2B PASTA domains are removed. Combined, our results show that the PBP2B PASTA domains are required to strengthen the interaction between PBP2B and DivIB.